Effect of a Sepsis Educational Intervention on Hospital Stay (2018)
Objectives: To evaluate adherence to the sepsis bundle before and after an educational strategy and its impact on hospital stay. Design: A prospective, analytic, before-and-after study of children with severe sepsis and septic shock who presented to the emergency department. Setting: Carried out from January to December 2014 in the emergency department of a quaternary care hospital. Patients: Of a total of 19,836 children who presented to the emergency department, 4,383 had an infectious pathology, with 203 of these showing severe sepsis and septic shock (124 pre intervention, and 79 post intervention). Interventions: The healthcare providers caring for the patients in pediatric emergency received an educational intervention and an update on the bundle concepts proposed in 2010 by the Pediatric Advanced Life Support program of the American Heart Association and adapted by this study's investigators. Measurements and Main Results: The main cause of sepsis in both groups was respiratory (59 vs 33; p = 0.72), without differences in the Pediatric Index of Mortality 2 score (7.23 vs 8.1; p = 0.23). The postintervention group showed a reduced hospital stay (11.6 vs 7.9 d; p = 0.01), a shorter time before ordering fluid boluses (247 vs 5 min; p = 0.001), the application of the first dose of antibiotic (343 vs 271 min; p = 0.03), and a decreased need for mechanical ventilation (20.1% vs 7.5%; p = 0.01). Postintervention adherence to the complete bundle was 19.2%, compared with the preintervention group, which was 27.7% (p = 0.17). Conclusions: Adherence to a bundle strategy is low following an educational intervention. However, when patients are managed after instruction in guideline recommendations, hospital stay may be significantly reduced. © 2018 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.